2014
DOI: 10.1089/acm.2013.0397
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Tissue Motion Induced by Acupuncture Needling Along Intermuscular Connective Tissue Planes

Abstract: Objectives: Acupuncture needle manipulation causes mechanical deformation of connective tissue, which in turn results in mechanical stimulation of fibroblasts, with active changes in cell shape and autocrine purinergic signaling. We have previously shown using ultrasound elastography in humans that acupuncture needle manipulation causes measurable movement of tissue up to several centimeters away from the needle. The goal of this study was to quantify the spatial pattern of tissue displacement and deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…The exact mechanism of how the fascial system mediates the therapeutic effect of motion acupuncture remains to be investigated. Current studies have shown that fibroblasts in fascia respond rapidly to acupuncture with active remodeling of their cytoskeleton and autocrine purinergic signaling, and modulating the composition and organization of extracellular matrix, which play an active role in regulating the connective tissue tension and viscoelastic relaxation, thereby reducing the musculoskeletal pain (28). Future studies would be needed to investigate how motion acupuncture is integrated into these pathways, as well as the molecular and cellular mechanism that underlies its therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of how the fascial system mediates the therapeutic effect of motion acupuncture remains to be investigated. Current studies have shown that fibroblasts in fascia respond rapidly to acupuncture with active remodeling of their cytoskeleton and autocrine purinergic signaling, and modulating the composition and organization of extracellular matrix, which play an active role in regulating the connective tissue tension and viscoelastic relaxation, thereby reducing the musculoskeletal pain (28). Future studies would be needed to investigate how motion acupuncture is integrated into these pathways, as well as the molecular and cellular mechanism that underlies its therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of acupuncture needle results in deformation of connective tissues and thus alters the structure of fibroblasts [ 197 , 261 , 262 , 263 , 264 ]. Such micro-injury caused by the puncturing of the acupuncture needle in the skin results in release of ATP [ 195 , 196 , 197 , 198 , 199 , 200 , 201 , 265 , 266 ].…”
Section: Mechanism Of Acupuncturementioning
confidence: 99%
“…Needle grasp allows further movements of the needle to pull and deform the connective tissue surrounding the needle, delivering some of its effects through mechanical influence on the connective tissue matrix [ 159 , 279 , 280 , 281 ]. In addition, the manipulation of the acupuncture needle causes remodeling of fibroblasts in the connective tissue [ 261 , 262 , 263 , 264 ].…”
Section: Mechanism Of Acupuncturementioning
confidence: 99%
“…Manipulation of acupuncture needle results in deformation of connective tissues and thus alters the structure of fibroblasts [197,[261][262][263][264]. Such micro-injury caused by the puncturing of the acupuncture needle in the skin results in release of ATP [195][196][197][198][199][200][201]265,266].…”
Section: Mechanism Of Acupuncturementioning
confidence: 99%